Cytotoxicity in L929 fibroblasts and inhibition of herpes simplex virus type 1 Kupka by estuarine cyanobacteria extracts - Viviana R Lopes (2011)
The cyanobacteria are known to be a rich source of metabolites with a variety of biological activities in different biological systems. In the present work, the bioactivity of aqueous and organic (methanolic and hexane) crude extracts of cyanobacteria isolated from estuarine ecosystems was studied using different bioassays. The assessment of DNA damage on the SOS gene repair region of mutant PQ37 strain of Escherichia coli was performed. Antiviral activity was evaluated against influenza virus, HRV-2, CVB3 and HSV-1 viruses using crystal violet dye uptake on HeLa, MOCK and GMK cell lines. Cytotoxicity evaluation was performed with L929 fibroblasts by MTT assay. Of a total of 18 cyanobacterial isolates studied, only the crude methanolic extract of LEGE 06078 proved to be genotoxic (IF > 1.5) in a dose-dependent manner and other four were putative candidates to induce DNA damage. Furthermore, the crude aqueous extract of LEGE 07085 showed anti- herpes type 1 activity (IC50 = 174.10 mu g dry extract mL(-1)) while not presenting any cytotoxic activity against GMK cell lines. Of the 54 cyanobacterial extracts tested, only the crude methanolic and hexane ones showed impair on metabolic activity of L929 fibroblasts after long exposure (48-72 h). The inhibition of HSV-1 and the strong cytotoxicity against L929 cells observed emphasizes the importance of evaluating the impact of those estuarine cyanobacteria on aquatic ecosystem and on human health. The data also point out their potential application in HSV-1 treatment and pharmacological interest.